PSIKOLOGI HUMANISTIK TOKOH UTAMA DALAM NOVEL SEKOTAK SENJA UNTUK NIRBITA KARYA YUPITAWDR - Ananto, Irfan; Yolanda; Fatimah (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This research aims to understand the aspects of literary psychology based on Maslow's theory and how humans achieve self-actualization. The research data is in the form of sentences containing elements of the hierarchy of human needs. The data collection techniques include reading, listening, and note-taking. The data analysis technique used is content analysis. The research results show that Nirbita's ego needs are the most dominant, with 22 data showing her desire to be valued, recognized, and express her feelings. The main factors influencing her psychological needs are a broken home situation, lack of self-confidence, fear and shame, rudeness, an unsupportive environment, and her introverted nature.